1974
DOI: 10.1099/00222615-7-4-411
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the  -Haemolysin of Staphylococcus Aureus

Abstract: PLATE XIXAT T E M P,T s by several investigators have failed to demonstrate the immunogenicity of the 6-haemolysin of StaphyZococcus aureus. Gladstone and Yoshida (1967) did not convincingly demonstrate that 8-lysin was immunogenic and they showed that inhibitors of its haemolytic activity were present in serum. Recent evidence suggests that these serum inhibitors are lipoproteins (Donahue, 1969;Kantor, Temples and Shaw, 1972).In this study, the immunogenicity of 8-lysin has been demonstrated by the use of pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1976
1976
1982
1982

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
2
16
1
Order By: Relevance
“…Anti-a haemolysin was not detectable in any of the sera tested, in contrast to the report of Fackrell and Wiseman (1974) that 6 haemolysin purified by the procedure of Kreger et al (1971) induced anti-a haemolysin in rabbits. Immunisation may provide a sensitive test for the presence of low levels of contamination in an immunising preparation; exclusion of the biologically potent a haemolysin is important when the biological properties of 6 haemolysin are being considered.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Anti-a haemolysin was not detectable in any of the sera tested, in contrast to the report of Fackrell and Wiseman (1974) that 6 haemolysin purified by the procedure of Kreger et al (1971) induced anti-a haemolysin in rabbits. Immunisation may provide a sensitive test for the presence of low levels of contamination in an immunising preparation; exclusion of the biologically potent a haemolysin is important when the biological properties of 6 haemolysin are being considered.…”
Section: Discussioncontrasting
confidence: 51%
“…Plommet and Bouillane (1966), Gladstone and Yoshida (1967), Hallander (1968) and Kantor, Temples and Shaw (1972) were unable to demonstrate an immune response to S haemolysin. More recently, antigenic and haemolysin-inhibitory activity has been demonstrated in IgG fractions of immune sera by Fackrell and Wiseman (1974), Birkbeck and Whitelaw (1976) and Heatley (1977). This paper describes properties of antisera to 6 haemolysin and some molecular measurements of 6 haemolysin.…”
Section: Plate Xi11mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the chromatographic procedures employed frequently yielded multiple peaks of 6 haemolysin, while crude preparations yielded only one peak of S haemolysin when tested electrophoretically and by molecular sieving. These findings, as well as those previously reported (Fackrell and Wiseman, 1974;Lee et al, 1976) clearly indicate the need to renew efforts to develop methods for the purification of 6 haemolysin.…”
Section: Discussionsupporting
confidence: 57%
“…They also found that the LDao of delta lysin for mice was 125 mg, although such a large LD, is meaningless except to suggest that the lysin is relatively non-toxic for mice. Calculations based on the data of Kreger et al (1971) give an LDm of 2 mg of delta lysin for mice and 7.2 mg for guinea pigs, but contamination of their preparations with alpha lysin at a concentration of one part in 2000 or less would account for these findings (see Fackrell & Wiseman, 1974).…”
mentioning
confidence: 99%